'A sort of Rathmines version of a Dior design': Maeve Brennan, Self-Fashioning and the Uses of Style. Issue 1 (2nd January 2016) - McWilliams, Ellen
Abstract: This article explores the politics of style in the writing of Maeve Brennan. Brennan's concern with style, subjectivity and power is strikingly visible in her short stories and 'Talk of the Town' essays for the New Yorker . While in some of her short stories published in the New Yorker in the 1950s, Brennan seems to offer an extended critique of dandyism, elsewhere in her writing self-fashioning takes on an altogether more positive value and is steeped in the political as well as literary commitments of her work. The article argues that Brennan's interest in the politics of style, both personally and in her writing, is informed by the different strategies she deployed as an Irish woman writer establishing her place amongst a New York literary elite in the mid twentieth century.